2010
DOI: 10.1002/cphc.201000187
|View full text |Cite
|
Sign up to set email alerts
|

On the Reactivity of Sulfosalts in Cyanide Aqueous Media: Structural, Bonding and Electronic Aspects

Abstract: The reactivity of the ruby silver minerals proustite (3Ag(2)S⋅As(2)S(3)) and pyrargyrite (3Ag(2)S⋅Sb(2)S(3)) was studied with two types of electrodes: a carbon-paste electroactive electrode (CPEE) and a paraffin-impregnated graphite electrode (PIGE). Polycrystalline samples of α-Ag(2)S (acanthite), As(2)S(3) (orpiment), Sb(2)S(3) (stibnite), Ag(3)AsS(3) (proustite), Ag(3)SbS(3) (pyrargyrite), and three samples of the proustite-pyrargyrite solid solution series were synthesized from pure elements by a solid-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…However, the reactivity of S n 2− and S 0 species on pyrite and other MS has been rarely investigated (Mikhlin et al 1998;Thomas et al 1998;Schaufuss et al 1998;Nava et al 2008;Meléndez et al 2010). Hence, the most active status of the eMPE surfaces was associated with the content, type and availability of S 0 species, as seen for pyrite and other MS studies (Nava et al 2008).…”
Section: Electrochemical Oxidation Of Unmodified Pyrite Surfacesmentioning
confidence: 95%
“…However, the reactivity of S n 2− and S 0 species on pyrite and other MS has been rarely investigated (Mikhlin et al 1998;Thomas et al 1998;Schaufuss et al 1998;Nava et al 2008;Meléndez et al 2010). Hence, the most active status of the eMPE surfaces was associated with the content, type and availability of S 0 species, as seen for pyrite and other MS studies (Nava et al 2008).…”
Section: Electrochemical Oxidation Of Unmodified Pyrite Surfacesmentioning
confidence: 95%
“…22,23 The Ag 3 SbS 3 phase is a p-type semiconductor with a bulk E g in the range of 1.8-2.0 eV. 24,25 It has wide applications in nonlinear optics and photocatalysts. 24,26 To our best knowledge, there has been no reports on the application of Ag 3 SbS 3 as a solar absorber material (preliminary photoelectrochemical study of Ag 3 SbS 3 has been explored, but no photovoltaic data were reported 27 ).…”
mentioning
confidence: 99%
“…Synthesis.-We synthesized Ag 3 SbS 3 with a modified procedure from Gonzalez et al, 10 as described before. 16 Typically, stoichiometric amounts of elemental silver (298.8 mg) and antimony (112.4 mg) were weighed and mixed thoroughly under argon.…”
Section: Methodsmentioning
confidence: 99%
“…A film prepared on a glass slide was used to obtain the diffuse spectra of the material with a cutoff consistent with the bandgap, E g = 2.0 eV previously reported. 10 An optical micrograph is given in supplementary material ( Figure S1). Figure 2 shows the SEM of the material synthesized after grinding; the images at different magnifications are consistent with an amorphous material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation